2015
DOI: 10.1103/physrevlett.114.232501
|View full text |Cite
|
Sign up to set email alerts
|

Observation ofHΛ4Hyperhydrogen by Decay-Pion Spectroscopy in Electron Scattering

Abstract: At the Mainz Microtron MAMI, the first high-resolution pion spectroscopy from decays of strange systems was performed by electron scattering off a 9 Be target in order to study the Λ binding energy of light hypernuclei. Positively charged kaons were detected by a short-orbit spectrometer with a broad momentum acceptance at zero degree forward angles with respect to the beam, efficiently tagging the production of strangeness in the target nucleus. In coincidence, negatively charged decay-pions were detected by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…A new measurement of the hypertriton bound state has been presented which points to a noticeably larger binding energy [73]. Measurements of 4 Λ H and 4 Λ He with improved accuracy in order to determine the amount of charge-symmetry breaking more precisely have been performed [63,71] or are on the way [94]. There are also attempts to shed more light on the elementary Y N interaction directly via studies of the Λp correlation function measured in heavy-ion collisions or high-energy pp collisions [95][96][97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new measurement of the hypertriton bound state has been presented which points to a noticeably larger binding energy [73]. Measurements of 4 Λ H and 4 Λ He with improved accuracy in order to determine the amount of charge-symmetry breaking more precisely have been performed [63,71] or are on the way [94]. There are also attempts to shed more light on the elementary Y N interaction directly via studies of the Λp correlation function measured in heavy-ion collisions or high-energy pp collisions [95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…We refrain from addressing the long-standing and still unsettled issue of the large charge symmetry breaking (CSB) [54,[68][69][70] observed in the binding energies of the 4 Λ He and 4 Λ H systems [63,71] here in detail. Indeed, there is no explicit CSB in the ΛN EFT potentials employed in the present study.…”
Section: Three-and Four-body Systemsmentioning
confidence: 99%
“…For example, binding energies of A = 3 and 4 hypernuclei can be obtained by solving "exact" Faddeev or Yakubovsky equations [1][2][3] based on such Y N interactions. So-called ab initio methods like the no-core shell model allow one to perform rigorous calculations even for hypernuclei beyond the s shell [4][5][6][7][8][9][10] and, so far, studies for hypernuclei up to 13 Λ C have been reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…This concerns also the binding energies of the A = 4 system where new measurements have been performed in an attempt to settle the long-standing issue of the large charge symmetry break-ing (CSB) observed in the binding energies of the 4 Λ He and 4 Λ H hypernuclei [12]. The new measurements, performed for the 4 Λ H (0 + ) state [13,14] and the splitting between the 4 Λ He 0 + and 1 + levels [15] differ noticeably from the earlier values in the literature [16]. Another binding energy that has been challenged lately is that of the hypertriton 3 Λ H. Here the value for the separation energy, accepted as benchmark for decades, is E Λ = 0.13±0.05 MeV [17], while a new measurement by the STAR collaboration suggests a value of 0.41 ± 0.12 MeV [18].…”
Section: Introductionmentioning
confidence: 99%
“…The source of this inconsistency is attributed to the charge symmetry breaking (CSB) in ΛN interaction. Recent reports on precise measurements for 4 Λ H at MAMI [1] and 4 Λ He at J-PARC [2] support the large CSB effect in the ΛN interaction suggested by old emulsion experiments.…”
Section: Introductionmentioning
confidence: 91%